PERAN MEDIASI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA HUBUNGAN ANTARA GOOD CORPORATE GOVERNANCE DENGAN NILAI PERUSAHAAN PERBANKAN INDONESIA PERIODE 2018 – 2020 - Muhammad Fahri Nugroho; Johny Subarkah; Muhammad Hasan Ma'aruf (Jurnal Akuntansi dan Pajak, 2022)
This study aims (1) to determine the effect of GCG on the company. (2) To reveal that CSR mediates the relationship between GCG and firm value. This study uses quantitative methods, namely secondary data that has been obtained tested using descriptive statistical tests based on the description of the company's performance in banking. The population in this study are the parties involved in companies listed on the IDX, namely banking companies. The samples used were listed companies, so the total sample for 3 years was 33 companies. The test equipment used in this research is to use a linear test which includes normality test, multicollinearity test, heteroscedasticity and autocorrelation. The results of this study indicate that: (1). GCG has an effect on firm value as shown in the table of coeficients, namely the t test for the GCG variable is known to have tcount (3.700) greater than ttable (2.040) or can be seen from the significance value of 0.001 < = 0 ,05. Therefore, Ho is rejected, meaning that GCG has a significant effect on firm value. (2) GCG has no simultaneous effect on CSR. From Table IV.2 it can be seen that the Fcount value is 0.238 (0.238 < Ftable 2.69) and p-value = 0.629 (> = 0.05). (3). shows that the CSR variable has a simultaneous effect on firm value. It also shows that the regression model used is fit of goodness. From Table IV.3 it can be seen that the Fcount value is 10,583 (10,583 > Ftable 2,69) and p-value = 0,003 (< = 0,05) (4) This shows that the GCG and CSR variables have a simultaneous effect on firm value. It also shows that the regression model used is fit of goodness. From Table IV.4 it can be seen that the Fcount value is 15.990 (15.990 > Ftable 2.69) and p-value = 0.000 (< = 0.05) . Keywords: CSR, GCG, Board of Commissioners, Independent Commissioner, Managerial Ownership, Company Size, ROA